Respostas
respondido por:
1
x.x + 2x = 35
x² + 2x - 35 = 0
delta = 2² - 4.1. (-35)
delta = 144
x = -2 +/- √144 / 2
x1= -2+12/2 = 5
x2= -2-12/2 = -7
substituindo na equação temos:
com x1 >
x² + 2x = 35
5² + 2.5 = 35
25 + 10 = 35
com x2 não daria o resultado certo.
Então o número é 5.
x² + 2x - 35 = 0
delta = 2² - 4.1. (-35)
delta = 144
x = -2 +/- √144 / 2
x1= -2+12/2 = 5
x2= -2-12/2 = -7
substituindo na equação temos:
com x1 >
x² + 2x = 35
5² + 2.5 = 35
25 + 10 = 35
com x2 não daria o resultado certo.
Então o número é 5.
Anônimo:
Obrigado viw gatinha <3
respondido por:
0
att. yrz
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás